Clinical features and morphology of collagen fibrils in patients with vascular Ehlers–Danlos based on electron microscopy - Ishikawa, Satoko; Hayashi, Shujiro; Sairenchi, Toshimi; Miyamoto, Manabu; Yoshihara, Shigemi; Kobashi, Gen; Yamaguchi, Tomomi; Kosho, Tomoki; Igawa, Ken (Frontiers in Genetics, 2023)
Background: Vascular-type Ehlers-Danlos syndrome (vEDS) is caused by collagen III deficit resulting from heterogeneous mutations in COL3A1, which occasionally causes sudden death due to arterial/visceral rupture. However, it is difficult to conduct basic research on the pathophysiology of vEDS. Moreover, the number of patients with vEDS is small, limiting the number of available samples. Furthermore, the symptoms of vEDS may vary among family members, even if they share the same mutation. Accordingly, many aspects of the pathology of vEDS remain unknown. Therefore, we investigated the structural abnormalities in collagen fibrils and endoplasmic reticulum (ER) stress in skin samples using electron microscopy as well as their relationship with clinical symptoms in 30 patients with vEDS (vEDS group) and 48 patients without vEDS (disease-negative control group). Methods: Differences between the two groups were evaluated in terms of the sizes of collagen fibrils using coefficient of variation (COV). Results: COV was found to be significantly higher in the vEDS group than in the disease-negative control group, indicating irregularity in the size of collagen fibrils. However, in the vEDS group, some patients had low COV and seldom experienced serious complications and ER stress. Conclusion: ER stress might affect collagen fibrilcomposing proteins. Moreover, as this stress varies among people based on environmental factors This is a provisional file, not the final typeset article and aging, it may be the underlying cause of varying vEDS symptoms.